System for Capture of Non-cooperative Spacecraft. Analysis and design - Humennyi, Dmytro; Khlaponin, Yurii; Marek, Aleksander (Vocational Training Center, 2022)
The Monography contains an overview of mechanical gripper systems to make a cooperative connection between spacecraft and Rocket. The middle of the Monography presents some ideas regarding the scenario of the capture of no-cooperative spacecraft. At the end of it - the main parts of the gripper have been described. Also, there are some roadmaps to design it based on the overviewed practices. Proceedings has been prepared by a team of authors consisting of PhD Dmytro Humennyi, Doctor of technical science, Professor Yurii Khlaponin, Doctor of technical science, Ing., Associate Professor Marek Aleksander. The text of the monograph was prepared using materials of the open press on the experience of foreign countries and Ukraine. For specialists involved in the development, creation and operation of spacecraft, it can also be recommended to graduate students and undergraduates. Edited by Academician of the Ukrainian Academy of Sciences, Doctor of Technical Sciences, Professor Y. Khlaponin.
Keywords: Non-cooperative Spacecraft; System for Capture; 629.78:004.45